Identification and Characterization of Probiotic Lactic Acid Bacteria Isolated from Indigenous Goat Milk - Setyawardani, T; Rahayu, WP; Maheswari, R; Palupi, NHS (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
Probiotic lactic acid bacteria play role as functional food and it is very important to know their identification and characterization. The diversity of lactic acid bacteria isolated from Ettawa crossbred and Saanen crossbreed goat milk was studied in terms of morphology, physiology and their characteristics. A total of 33 lactic acid bacterial strains were isolated and 18 isolates passed the initial selection.Â The second step was in vitro test, namely their resistances to low pH (2, 2.5, and 3.5) and bile salt (0.3%) were evaluated to know their potential as probiotic.Â The results showed that all strains grew well at acid condition (pH 2, 2.5, and 3.2) and seven strains grew well at bile salt (0.3%). Identification with API test for seven isolates showed that two isolates were Lactobacillus rhamnosus, 1 isolate was Lactobacillus plantarum and four isolates were Lactobacillus plantarum 1. (Animal Production 13 (1):57-63 (2011)Key Words: goat milk, lactic acid bacteria, probiotic, in vitro